Non-steroidal anti-inflammatory agents for cystoid macular oedema following cataract surgery: a systematic review. Issue 11 (18th October 2005) - Sivaprasad, S; Bunce, C; Wormald, R
Abstract : Aim: To examine the effectiveness of non-steroidal anti-inflammatory drugs (NSAIDs) in the treatment of cystoid macular oedema (CMO) following cataract surgery. Methods: Systematic literature review of randomised controlled trials (RCTs) that evaluated the effects of NSAIDs in the treatment of CMO following cataract surgery was done according to the Cochrane Collaboration methodology. Results: Seven trials involving a total of 266 participants were included. Four trials studied the effects of NSAIDs in chronic CMO while the other three trials examined the effect of NSAIDs in acute CMO. Little evidence of effectiveness was found for oral indomethacin and topical fenoprofen for chronic CMO in two small trials. Treatment with topical 0.5% ketorolac for chronic CMO was found to be effective in two trials. Three trials examined the effect of topical NSAIDs on acute CMO. The comparisons among these studies were of a NSAID to placebo, prednisolone or another NSAID. Because of considerable heterogeneity between these study designs, their results were not combined in a meta-analysis. Conclusion: A positive effect of topical NSAID (0.5% ketorolac tromethamine ophthalmic solution) on chronic CMO was noted. However, there is not enough evidence to show the effectiveness of NSAIDs in acute CMO following cataract surgery.